2011
DOI: 10.1002/dvg.20815
|View full text |Cite
|
Sign up to set email alerts
|

Generation of Ppp2Ca and Ppp2Cb conditional null alleles in mouse

Abstract: Protein phosphatase 2A (PP2A) is one of the most abundant serine/threonine phosphatases, with a critical role in embryonic development and human disease. There are two isoforms of the catalytic subunit of PP2A, Ppp2ca and Ppp2cb. Null mutation of Ppp2ca leads to early embryonic lethality at E6.5, hindering functional study of PP2A beyond this stage. We generated conditional null alleles of Ppp2ca and Ppp2cb by flanking with loxP sites exons 3 to 5 of Ppp2ca and exon 3 of Ppp2cb. Ppp2ca(fl/fl) mice did not disp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 18 publications
1
36
0
Order By: Relevance
“…Previous studies have shown that Ppp2ca is expressed at a higher abundance than Ppp2cb in most human tissues 7 and the dominant functions of PP2Aca cannot be compensated by PP2Acb in embryonic development, the liver, or the heart. [8][9][10][11][12] From our data, a single knockout of Ppp2ca or Ppp2cb in oocytes resulted in normal fertility, revealing that each PP2Ac could support oocyte maturation by itself. We suspect that PP2Acb may exist as a backup regulator for PP2Aca to regulate cell division in both meiosis and mitosis, which can only be revealed when PP2Aca and PP2Acb are simultaneously depleted.…”
Section: Pp2aca and Pp2acb Compensate Each Other To Support Oocyte Mamentioning
confidence: 61%
See 2 more Smart Citations
“…Previous studies have shown that Ppp2ca is expressed at a higher abundance than Ppp2cb in most human tissues 7 and the dominant functions of PP2Aca cannot be compensated by PP2Acb in embryonic development, the liver, or the heart. [8][9][10][11][12] From our data, a single knockout of Ppp2ca or Ppp2cb in oocytes resulted in normal fertility, revealing that each PP2Ac could support oocyte maturation by itself. We suspect that PP2Acb may exist as a backup regulator for PP2Aca to regulate cell division in both meiosis and mitosis, which can only be revealed when PP2Aca and PP2Acb are simultaneously depleted.…”
Section: Pp2aca and Pp2acb Compensate Each Other To Support Oocyte Mamentioning
confidence: 61%
“…The PP2Aca-null zygote is embryonic lethal, whereas the PP2Acb-null mouse has no obvious abnormality. 10 The function of PP2Acb has never been demonstrated. Previous studies have shown that Ppp2ca is expressed at a higher abundance than Ppp2cb in most human tissues 7 and the dominant functions of PP2Aca cannot be compensated by PP2Acb in embryonic development, the liver, or the heart.…”
Section: Pp2aca and Pp2acb Compensate Each Other To Support Oocyte Mamentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the loss of Ppp2ca results in the absence of mesodermal germ layer, indicating defect in embryo differentiation. Interestingly, Ppp2cb knockout mice model showed no abnormal phenotype [93]. Thus, the results from these knock-out mouse models indicated that while Ppp2ca is essential for the developmental process in the mouse, Ppp2cb is not.…”
Section: Mouse Models Relevant To Pp2a Subunitsmentioning
confidence: 99%
“…PP2A exists in the cytosol primarily as a heterodimer consisting of a catalytic (C) and a scaffolding (A) subunit, to which a variety of targeting or regulatory (B) subunits associate, altering the specificity of the phosphatase [12], [13]. The complexity of PP2A composition arises from the enormity of distinct PP2A holoenzyme assemblies formed by proteins coded by the two similar yet non-redundant genes responsible for the catalytic subunit [14], [15], the two non-redundant genes coding for the scaffolding subunit [16], [17], and the four unrelated families of regulatory subunits encoded by multiple genes with a variety of splice variants giving rise to at least 23 different B subunits [10], [11], [18], [19], [20]. The vast array of subunits available for integration into PP2A holoenzymes are themselves regulated by spatial and temporal means as well as a strict regimen of posttranslational modifications [10], [21].…”
Section: Introductionmentioning
confidence: 99%